Optimalisasi Sosialisasi Pemanfaatan Aspek Hukum Kepada Pelaku Usaha UMKM Desa Sukaratu Kecamatan Cikeusal Kabupaten Serang - Walid Mujtahidin; Fitria Agustin (jurnal ABDIMAS Indonesia, 2023)
Community Service carried out in this activity is a special form of community service activity that prioritizes three principles, namely education or teaching, research and community service. Implementation of Incidental Service Activities in 2023 with the theme "Innovation and Digitalization of MSMEs Towards an Independent Society in Accordance with Legal Aspects of Business" implementation of activities in Sukaratu Village for 1 day, namely 10 September 2023. In accordance with legal functions (social control and social engineering), there are various problems in discussions that need to be given a legal umbrella. The primary function of law is to protect people from dangers and actions that can harm and suffer the lives of other people. By looking at the problems regarding MSMEs in Sukaratu Village, we provide solutions to overcome these problems so that MSMEs can develop their businesses more advanced and more modern. The solution offered was to provide information related to business aspects for MSME actors in Sukaratu village, and this solution was also very enthusiastically accepted by MSME actors in this service activity.